ANALISIS KESIAPAN SDM KESEHATAN DALAM MENCAPAI TARGET ELIMINASI TUBERKULOSIS DI PROVINSI NUSA TENGGARA TIMUR - Yustins Rindu; Dominggus Gonsalves; Sabinus Bungaama Kedang; Simon Sani Kleden; Febtian Cendradevi Nugroho; Maria Agustina Making; Yakobus Beda Kleden; Christina Grasia Kellen (Bajang Institute, 2026)
This study aims to analyze the readiness of health human resources (HRH) in East Nusa Tenggara (NTT) Province to achieve the tuberculosis (TB) elimination target by 2030. A descriptive analytic design with quantitative and qualitative approaches was applied, using secondary data from the Global Tuberculosis Report 2023 (WHO), National TB Control Program Report 2023 (Ministry of Health, Indonesia), and NTT Health Profile 2023 (BPS). Results show that HRH ratios in NTT remain below national standards, with TB drug-sensitive treatment success at 84% and drug-resistant TB treatment success at 56%. Preventive therapy coverage for household contacts reached only 37%. The study concludes that strengthening HRH through recruitment, redistribution, continuous training, and community cadre empowerment is essential to achieve TB elimination by 2030.